Robot-assisted tubal reanastomosis: Initial experience in a single institution - Ahmet Göçmen; Fatih Şanlıkan; Mustafa Gazi Uçar (Elsevier, 2013)
Objective: To assess surgical outcomes for robot-assisted tubal reanastomosis in a single institution. Materials and Methods: Between March 2009 and January 2010, 10 patients underwent robot-assisted tubal ligation reversal (TLR) with a da Vinci S surgical system. Patient demographic data, including operative times, operative and postoperative complications, hospital stay, conversion to laparotomy and pregnancy rates were recorded. Results: Mean age and body mass index for the patients were 37.7 (35-42) years and 28.9 (23.9-36.3) kg/m2, respectively. The mean console time was 102.5 min and the mean total operation time was 130.6 (102-164) min. The mean hospital stay was 1.2 (1-2) days. There were no significant intra-operative or early-postoperative complications. All surgeries were completed robotically with no conversion to laparotomy. There were seven subsequent pregnancies in the study participants, representing a pregnancy rate of 70%, of which five were intrauterine pregnancies, one was an ectopic pregnancy, and one was an abortus. Conclusion: Robot-assisted TLR is safe and feasible. This procedure may facilitate minimally invasive treatment for patients who want to regain their fertility without the aid of artificial reproductive techniques.